Analysis, Modeling and Simulation of Multiscale Problems
DOI: 10.1007/3-540-35657-6_22
|View full text |Cite
|
Sign up to set email alerts
|

Motion of Electrons in Adiabatically Perturbed Periodic Structures

Abstract: We study the motion of electrons in a periodic background potential (usually resulting from a crystalline solid). For small velocities one would use either the non-magnetic or the magnetic Bloch hamiltonian, while in the relativistic regime one would use the Dirac equation with a periodic potential. The dynamics, with the background potential included, is perturbed either through slowly varying external electromagnetic potentials or through a slow deformation of the crystal. In either case we discuss how the H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Let us also remark that while we take the more explicit approach of using Bloch waves in a modified FGA ansatz for periodic media, as in (3.8). The same approximation can be also derived by first projecting the whole Schrödinger equation using a super-adiabatic projection as developed in [29,30] and then apply the frozen Gaussian approximation to the resulting dynamics. We will not go into the details in this work.…”
Section: Formulation and Main Resultsmentioning
confidence: 99%
“…Let us also remark that while we take the more explicit approach of using Bloch waves in a modified FGA ansatz for periodic media, as in (3.8). The same approximation can be also derived by first projecting the whole Schrödinger equation using a super-adiabatic projection as developed in [29,30] and then apply the frozen Gaussian approximation to the resulting dynamics. We will not go into the details in this work.…”
Section: Formulation and Main Resultsmentioning
confidence: 99%
“…denotes the so-called Berry phase term (Carles et al 2004, Panati, Spohn andTeufel 2006), which is found to be purely imaginary β m (t, x) ∈ (iR) d . It is, importantly, related to the quantum Hall effect (Sundaram and Niu 1999).…”
Section: Two-scale Wkb Approximationmentioning
confidence: 99%
“…Note that in (3.10e) A m = ∇ ξ Φ m , Φ m is the so-called Berry-connection [12,35]. Notice that we have gauge freedom in choosing Bloch functions, i.e.…”
Section: The Bloch Decomposition-based Gaussian Beam Methodsmentioning
confidence: 99%
“…To consider the Schrödinger equation in the quasi-momentum space, we introduce a new functionψ ε by taking the Bloch transformation [35,21] T of the wave function ψ ε as…”
Section: The Schrödinger Equation Under the Bloch Transformationmentioning
confidence: 99%
See 1 more Smart Citation